2016
DOI: 10.1063/1.4965916
|View full text |Cite
|
Sign up to set email alerts
|

Modulus–pressure equation for confined fluids

Abstract: Ultrasonic experiments allow one to measure the elastic modulus of bulk solid or fluid samples. Recently such experiments have been carried out on fluid-saturated nanoporous glass to probe the modulus of a confined fluid. In our previous work [J. Chem. Phys., (2015) 143, 194506], using Monte Carlo simulations we showed that the elastic modulus K of a fluid confined in a mesopore is a function of the pore size. Here we focus on modulus-pressure dependence K(P), which is linear for bulk materials, a relation kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(84 citation statements)
references
References 67 publications
6
77
1
Order By: Relevance
“…where, in our case, P is the solvation pressure in the fluid phase, P 0 is some reference pressure, and K T = dK T /dP , which is constant in the first approximation. This dependence holds for confined fluids as well [22,33], moreover with the same slope K T [24]. The solvation pressure P in the confined fluid (not to be confused with vapor pressure p) consists of two terms [52]: the solidfluid interaction term and Laplace pressure…”
Section: Discussionmentioning
confidence: 86%
“…where, in our case, P is the solvation pressure in the fluid phase, P 0 is some reference pressure, and K T = dK T /dP , which is constant in the first approximation. This dependence holds for confined fluids as well [22,33], moreover with the same slope K T [24]. The solvation pressure P in the confined fluid (not to be confused with vapor pressure p) consists of two terms [52]: the solidfluid interaction term and Laplace pressure…”
Section: Discussionmentioning
confidence: 86%
“…133,134 In particular, it was shown that the change in the elastic modulus of the adsorbed fluid is linearly related to the adsorption stress in the pores. 135,136 E. Surface stress approach…”
Section: Coupling Between Thermodynamic and Elastic Aspects Of Adsmentioning
confidence: 99%
“…An additional challenge is that the measurement of the PSD ℱ ( w , μ 1 , p , T ) would necessitate measurements of the PSD at single pressures, which is not possible with existing adsorbent characterization techniques. Recent work by Gor et al [1416] discusses relationships between pore size and the compressibility of a liquid-like confined fluid, measured at a single pressure, which might be further developed to compute the PSD of a material using single-pressure measurements. Such a method could provide the single-pressure measurements essential to application of the statistical mechanics presented here.…”
Section: Discussionmentioning
confidence: 99%